2005
DOI: 10.1111/j.1467-937x.2005.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative Externalities and Evolutionary Implementation

Abstract: We model externality abatement as an implementation problem. A social planner would like to ensure efficient behaviour among a group of agents whose actions are sources of externalities. However, the planner has limited information about the agents' preferences, and is unable to distinguish individual agents except through their action choices. We prove that if a concavity condition on aggregate payoffs is satisfied, the planner can guarantee that efficient behaviour is globally stable under a wide range of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 21 publications
0
53
0
Order By: Relevance
“…We discuss their work at the end of this section. 4 Some papers related to application of evolutionary game theory are on externality pricing and macroeconomic spillovers (Sandholm (2002(Sandholm ( , 2005), natural selection and animal behavior (Maynard Smith (1982), Hofbauer and Sigmund (1988)), congestion in highway and computer networks (Monderer and Shapley (1996), Sandholm (2001)), emergence of residential segregation (Dokumaci and Sandholm (2007)). …”
mentioning
confidence: 99%
“…We discuss their work at the end of this section. 4 Some papers related to application of evolutionary game theory are on externality pricing and macroeconomic spillovers (Sandholm (2002(Sandholm ( , 2005), natural selection and animal behavior (Maynard Smith (1982), Hofbauer and Sigmund (1988)), congestion in highway and computer networks (Monderer and Shapley (1996), Sandholm (2001)), emergence of residential segregation (Dokumaci and Sandholm (2007)). …”
mentioning
confidence: 99%
“…An important special case is based on random matching in a symmetric normal form game with payoff matrix A ∈ R n×n ; in this case, the payoff function is the linear function π(x) = Ax. More generally, our setup also allows the payoffs to each action to depend nonlinearly on the population state, a feature that is essential in some applications-see Sandholm (2004).…”
Section: Common Preferencesmentioning
confidence: 99%
“…Roberts showed that such rules must satisfy a monotonicity condition, called PAD. Using our notation, his proof relies on the following technical result 21 : Theorem A (Roberts 1979): Let X = R K N and assume that K 3. Then any function : X !…”
Section: Potentials and Potential Gamesmentioning
confidence: 99%
“…Thus, statements over implementable choice rules can be translated into statements about best-alternative potentials 5 . Ordinal potentials go beyond ex-post implementation by requiring that, after eventual transfers, agents agree over the ranking of all alternatives (rather than just the best alternative), and 2 In contrast, Sandholm (2005) shows how a price scheme administered by a designer can be used to augment an externality abatement game in order to yield a potential game a la Monderer-Shapley. A dynamic learning process leads there to an e¢ cient outcome.…”
Section: Introductionmentioning
confidence: 99%